Dead, but still breathing: the problem of postmortem movement in horror films. Issue 2 (3rd April 2018) - Diffrient, David Scott
Abstract: This article builds upon Davina Quinlivan's pioneering work on cinematic breathing by considering the conspicuous but often-overlooked place of breath in horror films. The author focuses specifically on the way still-breathing bodies – i.e. those of actors pretending to be deceased on screen – prick our senses and draw our attention to one of the genre's unavoidable paradoxes. Stated simply, what all but the most metatextual or parodic horror films wish to hide – to keep concealed inside their own literal and figurative 'basements' – is the inherent artifice of fictional death, which has traditionally been represented by way of living actors who must mask their breathing in order to sustain the feeling of dread on which the genre is affectively reliant. Taking the title and premise of the recent U.S. theatrical release Don't Breathe (2016) as a leaping-off point, but expanding the scope of this essay to include a representative cross section of international productions and trashy exploitation cinema, the author hopes to contribute to a better understanding of the genre's unique respiratory tendencies as well as the risible yet significant textual ruptures that occur when bodies continue breathing after they have stopped living.